Psychological Portrayal Of Women Characters In The Novels Of Anita Desai - et. al., Shweta, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this paper is to examine the status of Indian women mind, their womanhood and their mental underpinnings. It talks about how Desai's Indian ladies have endured because of their families and the general public that leave them with no other option yet to capitulate to mental sickness in isolation. Anita Desai has introduced various phases of human brain research particularly of ladies. Her range is very wide. Her characters are from the ladies of all age group. Her female characters face personality emergency and different experiences and that at last lead in suicide and demise. Their journey of self-revelation is cultivated distinctly through offense. This paper dissects how the disruption of phallogocentric account and landscapes involve the attack of connection among sexual orientation and re- conceptualization of female want. Such catastrophe is because of disappointment endeavor a re-conceptualization among fantasy and reality.